KOMUNIKASI PEMBERDAYAAN KELOMPOK PETANI IKAN GURAMI DESA BEJI, KEDUNGBANTENG, BANYUMAS - Dewi Astuti (CV. Amerta Media, 2019)
Empowerment of rural communities can increase the potential and creativity of the community in improving their standard of living. This study aims to explain the empowerment program to groups of fish farmers in Beji village, Kedungbanteng District, Banyumas Regency, Central Java. Using the survey method, the case study approach is descriptive analysis. The method of collecting data through observation, interviews and documents. The result is an empowerment model that is conducted in the form of training (counseling) for gouramy cultivation by the ministry of maritime affairs and fisheries in collaboration with village officials. Beji village government also provides cheap rental facilities to farmer groups included in this empowerment group. Pellet making equipment (fish food) is also provided by the ministry of maritime affairs and fisheries with pellet making training. Empowerment communication is interpersonal communication and group communication (direct communication, consultation in training).Key Words: empowerment, empowerment communication, farmer groups